Malaysian Coins Recognition Using Machine Learning Methods - Zainuddin N.N.; Azhari M.S.N.B.N.; Hashim W.; Alkahtani A.A.; Mustafa A.S.; Alkawsi G.; Noman F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Adaptive boosting; Discriminant analysis; Machine learning; Nearest neighbor search; Neural networks; Classifieds; Coin recognition; Complex Processes; Daily lives; Images processing; Machine learning approaches; Machine learning methods; Malaysians; Object categories; Training model; Image processing